Platelet Aggregation in Finnish Men and Its Relation to Fatty Acids in Platelets, Plasma and Adipose Tissue - Salo, M K; Vartiainen, E; Puska, P; Nikkari, T (Thrombosis and Haemostasis, 1985)
Platelet aggregation and its relation to fatty acid composition of platelets, plasma and adipose tissue was determined in 196 randomly selected, free-living, 40-49-year-old men in two regions of Finland (east and southwest) with a nearly twofold difference in the IHD rate.There were no significant east-southwest differences in platelet aggregation induced with ADP, thrombin or epinephrine. ADP-induced platelet secondary aggregation showed significant negative associations with all C20-C22 ω3-fatty acids in platelets (r = -0.26 - -0.40) and with the platelet 20: 5ω3/20: 4ω 6 and ω3/ ω6 ratios, but significant positive correlations with the contents of 18:2 in adipose tissue (r = 0.20) and plasma triglycerides (TG) (r = 0.29). Epinephrine-induced aggregation correlated negatively with 20: 5ω 3 in plasma cholesteryl esters (CE) (r = -0.23) and TG (r = -0.29), and positively with the total percentage of saturated fatty acids in platelets (r = 0.33), but had no significant correlations with any of the ω6-fatty acids. Thrombin-induced aggregation correlated negatively with the ω3/6ω ratio in adipose tissue (r = -0.25) and the 20: 3ω6/20: 4ω 6 ratio in plasma CE (r = -0.27) and free fatty acids (FFA) (r = -0.23), and positively with adipose tissue 18:2 (r = 0.23) and 20:4ω6 (r = 0.22) in plasma phospholipids (PL).The percentages of prostanoid precursors in platelet lipids, i. e. 20: 3ω 6, 20: 4ω 6 and 20 :5ω 3, correlated best with the same fatty acids in plasma CE (r = 0.32 - 0.77) and PL (r = 0.28 - 0.74). Platelet 20: 5ω 3 had highly significant negative correlations with the percentage of 18:2 in adipose tissue and all plasma lipid fractions (r = -0.35 - -0.44).These results suggest that, among a free-living population, relatively small changes in the fatty acid composition of plasma and platelets may be reflected in significant differences in platelet aggregation, and that an increase in linoleate-rich vegetable fat in the diet may not affect platelet function favourably unless it is accompanied by an adequate supply of ω3 fatty acids.
Keywords: Platelet aggregation; Fatty acids; Lipids; Linoleic acid; Arachidonic acid; Eicosapentaenoic acid